A new Microelectronic Engineering degree curriculum in KUKUM - Yufridin, Wahab; Ali Yeon, Md Shakaff; Zul Azhar, Zahid Jamal; Zuraidah, Mohd Zain; Reha, Abdul Razak; Uda, Hashim (Association of Engineering Education in South East Asia and the Pacific, 2009)
Organized by Association of Engineering Education in South East Asia and the Pacific, 8th - 9th December 2005 at Hotel Istana, Kuala Lumpur.